From state planning to public contracting: a necessary option for susteinable development - Silva, André Ricardo Fonseca da; Bahia, Bruno Gomes (Direito e Desenvolvimento, 2019)
This article is about analyzing the state dynamics that goes from planning, through the public budget, to materialize with public procurement. Its focus is to find, in each of these institutes linked to the economic and financial order, its point of intersection with sustainable development, defended in the present work as one of the fundamental principles of the Republic, through the intertwining of arts. 1º, 3º, 170 and 225 of the Constitution. From this, it sheds some light on what is called sustainable public procurement, calling attention to the state purchasing power, which, because of the large volume of resources it moves, can be an important tool to induce and influence the market to a more sustainable behavior. Thus, recognizing the socio-environmental crisis suffered by the planet, it is intended to articulate forces to develop a culture oriented to reconcile the dimensions of sustainability, especially its economic, social and environmental aspects. Thus, adopting a qualitative research methodology of bibliographic review, it was concluded that, from planning to hiring, the State necessarily needs to opt for sustainable development, under penalty of aggravation of the socio-environmental crisis or even make the effort in sustainable public procurement mere initiatives in the field of public administration.